The effectiveness of S-100 ECDIS capable of ENDS in the view of ship officers’ visual characteristics - Jang, Junhyuk; Park, Sekil; Oh, Sewoong; Kim, Iji (The International Hydrographic Review, 2025)
The development of electronic chart display and information systems (ECDIS) has enabled conversion of nautical charts from paper publications to electronic format. Because the International Maritime Organization (IMO) has mandated the installation of ECDIS in ships engaged in international navigation, the effectiveness of the newly introduced S-100 ECDIS must be determined using electronic equipment, compared with traditional navigation preparation tasks. Here, the effectiveness of the S-100 ECDIS, capable of Electronic Navigational Data Service (ENDS), was compared with the effectiveness of the existing ECDIS and traditional nautical publications by analyzing the visual performance of ship officers during tasks involved in developing a voyage plan. This study showed that the S-100 ECDIS with ENDS is more effective than the S-57 ECDIS with nautical publications. The improvement in voyage planning using the S-100 ECDIS was demonstrated by ship officers’ visual performance.